Czy endotelina-1 i neuropeptyd Y odgrywają rolę w patogenezie neuropatii jaskrowej? - Terelak-Borys, Barbara (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Vasospasm in the vessels, supporting the optic disc, is nowadays considered one of the possible etiological factors leading to development of glaucomatous neuropathy. This article describes physiological regulatory mechanisms of blood circulation in these vessels, including influence of autonomic nervous system and blood flow autoregulation; it also explains why vasospasm may disturb autoregulation. Special attention is paid to the role of vascular endothelial mediators, which are responsible for autoregulation. Observations indicating that vasospasm may be a risk factor of glaucomatous damage are also presented. The article describes data concerning vasospastic effects of two mediators: endothelin-1 (ET-1), released by vascular endothelium, and neuropeptide Y (NPY), a sympathetic nervous system neurotransmitter, on the vessels supporting the optic disc and their possible role in producing blood flow disturbances in these vessels. Investigation results indicating that endothelial dysfunction, connected with increased ET-1 plasma levels and sympathetic nervous system disorders, may be involved in the pathogenesis of normal-tension glaucoma, are presented.